Cloud Computing: A Paradigm Shift - SEOW, Poh Sun (Institutional Knowledge at Singapore Management University, 2012)
Research has shown that investment in IT is a key driver of productivity improvement in the accountancy sector. IT enables accounting firms to increase their productivity by automating tasks and enhancing collaboration within the firm and with their clients. Cloud computing has generated much interest from the business and IT communities these days as an emerging technology to increase productivity.